The Influence of Service Quality and Product Quality on Consumer Loyalty with Consumer Satisfaction as Moderating Variable at PT. Mabar Feed Indonesia - Ryan Wijaya; Sofiyan Sofiyan; Yusuf Ronny Edward; Nagian Toni (Privietlab, 2022)
PT. Mabar Feed Indonesia is one of the companies engaged in the poultry feed industry for laying hens and meat. Other products produced by PT. Mabar Feed Indonesia in the form of shrimp and other animal feed. This study uses a quantitative approach with SPSS tools. This study found that service quality has a significant effect on consumer loyalty at PT. Mabar Feed Indonesia. Product quality has a significant effect on consumer loyalty at PT. Mabar Feed Indonesia. Service quality has an effect on consumer loyalty with consumer satisfaction as a moderating variable at PT. Mabar Feed Indonesia. Product quality affects consumer loyalty with consumer satisfaction as a moderating variable at PT. Mabar Feed Indonesia.